2017
DOI: 10.1371/journal.pone.0181822
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo anti-inflammatory active copper(II)-lawsone complexes

Abstract: We report in vitro and in vivo anti-inflammatory activities of a series of copper(II)-lawsone complexes of the general composition [Cu(Law)2(LN)x(H2O)(2-x)]·yH2O; where HLaw = 2-hydroxy-1,4-naphthoquinone, x = 1 when LN = pyridine (1) and 2-aminopyridine (3) and x = 2 when LN = imidazole (2), 3-aminopyridine (4), 4-aminopyridine (5), 3-hydroxypyridine (6), and 3,5-dimethylpyrazole (7). The compounds were thoroughly characterized by physical techniques, including single crystal X-ray analysis of complex 2. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Pomiferin itself did not increase the amount of ROS in both experiments. Similar behaviour was also observed previously for heteroleptic copper(II) complexes containing 1,4-naphthoquinone derivative lawson [54].…”
Section: Intracellular Production Of Reactive Oxygen Species (Ros)supporting
confidence: 89%
See 1 more Smart Citation
“…Pomiferin itself did not increase the amount of ROS in both experiments. Similar behaviour was also observed previously for heteroleptic copper(II) complexes containing 1,4-naphthoquinone derivative lawson [54].…”
Section: Intracellular Production Of Reactive Oxygen Species (Ros)supporting
confidence: 89%
“…The relative cell viability of floating monocytes THP-1 were determined after 24 h incubation in a serum-free medium with compounds 1 – 5 dissolved in N , N -dimethylformamide (DMF) at increasing concentrations (20–0.125 µM) by the cell proliferation reagent WST-1 (Roche, Basel, Switzerland) according to the manufacturer’s manual, as we described previously [ 54 ]. The IC 50 values were calculated from resultant viability curves by four-parameter logistic (4PL) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An experimental study realized by Ait El Cadi et al demonstrated that ethanolic and aqueous extracts of Z. gaetulum L reduce inflammation in edema induced by carrageenan [44]. In another hand, Liou et al confirmed anti-inflammatory activity of two components (lawsochylin 1 and lawsonaphthoate A) from L. inermis these molecules inhibit superoxide anion generation in inflammation process [45]. Plants that were identified as having hallucinogenic effects belong to three species, namely, H. muticus L., D. stramonium L., and M. fragrans L. These results are in accordance with the well-established result of toxicological studies showing hallucination symptoms appearing following ingestion of high doses of H. muticus and D. stramonium L. [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of NF-κB transcription factors was evaluated on THP1-Blue™ NF-κB cells as described previously [50,51]. Briefly, cells were transferred into serum-free RPMI 1640 medium as was delineated above in Section 3.4.…”
Section: Determination Of Nf-κb Activitymentioning
confidence: 99%
“…To differentiate THP1-Blue™ NF-κB monocytes into macrophages, the cells were stimulated with phorbol myristate acetate (PMA) at the final concentration of 50 ng/mL, as was described previously [51,52]. Cells were seeded into 8-well cell culture glass slide (SPL, Korea) at the concentration of 500,000 cells/mL, 150,000 cells per well.…”
Section: Immunocytochemical Analysis Of Nf-κb Nuclear Migrationmentioning
confidence: 99%